Download presentation

Presentation is loading. Please wait.

1
Substitution

2
**Take OUT the variable and PUT in the new expression**

y = 4x + 1 2x – y = 9 y = -2x -3 y = 6x + 1 y = 4x + 1 2x – y = 9 y = -2x - 3 y = 6x +1 2x – (4x + 1) = 9 -2x – 3 = 6x + 1

3
**Take OUT the variable and PUT in the new expression**

y = 4x + 1 2x – 2y = 9 x = -2x -3 y = 6x + 1 y = 4x + 1 2x – 2y = 9 x= -2x - 3 y= 6x +1 2x – 2(4x + 1) = 9 y = 6(-2x – 3) + 1

4
**Write the NEW equation after you substitute.**

Your Turn! Write the NEW equation after you substitute.

5
y = 6x – 11 -2x – 3y = -7 -2x – 3(6x-11) = -7

6
2x – 3y =-1 y = x - 1 2x – 3(x-1) = -1

7
y = -3x +5 5x – 4y = -3 5x – 4(-3x + 5) = -3

8
**(-5x-17) = -x – 1 or (-x – 1) = -5x - 17**

y = -x -1 Y = -5x - 17 (-5x-17) = -x – 1 or (-x – 1) = -5x - 17

9
y = -2 4x – 3y = 18 4x – 3(-2) = 18

10
x= -2y x – 2y = -13 -7(-2y + 11) – 2y = -13

11
y = -5x – 21 y = 4x +6 (-5x - 21) = 4x + 6 or (4x + 6) = -5x - 21

12
y = 1/2x – 2 -5x + y = -2 -5x + (1/2x-2) = -2

13
x = -3y x – 3y = -15 -3(-3y + 1) – 3y = -15

Similar presentations

Presentation is loading. Please wait....

OK

Addition Facts 1 - 20.

Addition Facts 1 - 20.

© 2018 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google